The Use of Drop-Structures to Increase the Dissolved Oxygen Level along the Cibarani Channel - Jonathan Wijaya; Doddi Yudianto; Finna Fitriana (Journal of the Civil Engineering Forum, 2021)
The Cikapundung river basin community uses the Cibarani channel as a drainage system and water source for fishing. However, the test result released on 9th November 2020 revealed that the channel’s water quality failed to reach the class II raw water standards due to various domestic waste discharges. This led to the performance of various studies to identify pollution control techniques by limiting the wastewater discharge and quality, controlling the intake discharge, and using baffles. The Cibarani channel has a drop-structure that can improve the water quality, though the effect has not been previously detailed. Therefore, this study was intended to comprehensively examine the effect of the drop-structure along the Cibarani channel to improve water quality conditions, specifically the Dissolved Oxygen (DO) parameter. This study employed the one-dimensional HEC-RAS software to simulate the hydrodynamic and water quality conditions along the Cibarani channel, and the drop-structure was modelled using two alternatives consisting of a vertical wall and a steep riverbed. Subsequently, the drop-structure fitted with a vertical wall gave a more plausible reaeration rate of 125 day-1 and Root Mean Square Error (RMSE) value of 0.50. The placement of a similar configuration before the first housing of the channel increased the DO concentrations by an average of 4.37 mg/L. This was followed by the modelling of another drop-structure after the first housing to increase the DO levels at the downstream part. Eventually, the combination of the two new drop-structures succeeded in increasing the DO concentrations along the Cibarani channel to 3.3 - 6.9 mg/L.